3-Benzyl-1-{[3-(4-chlorophenyl)isoxazol-5-yl]methyl}-1H-benzimidazol-2(3H)-one - Youssef Kandri Rodi; Amal Haoudi; Frédéric Capet; Christian Rolando; Lahcen El Ammari (Acta Crystallographica Section E, 2013)
In the title compound, C24H18ClN3O2, the benzimidazole plane is nearly perpendicular to the phenyl ring and to the isoxazole ring, making dihedral angles of 75.95 (7) and 73.04 (8)°, respectively, but the two residues point in opposite directions with respect to the benzimidazole plane. The dihedral angle between the chlorophenyl and isoxazole rings is 7.95 (8)°. In the crystal, molecules are linked by pairs of C—H...O hydrogen bonds into inversion dimers.